Improving Fourth-Grade Students’ Science Learning Outcomes and Motivation through Experimental Methods with a Deep Learning Approach: A Classroom Action Research Study - Paradika Angganing (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Background: Experimental learning combined with a pedagogical through deep learning approach is a new activity in elementary school. This deep learning approach in pedagogic activities encourages students to conduct experiments in the classroom through Sciences subjects. Aim: This study aims to improve science subject outcomes and learning motivation by using experimental methods and pedagogical through deep learning approaches. Method: This study is a Classroom Action Research (CAR) which conducted in two cycles. Each cycle is conducted twice. The number of subjects in this consisting of eighteen students. Data collection was using tests and non-tests. Data collection instruments were test items, observation sheets, and document checklists. Data analysis techniques were descriptive comparative analysis techniques and critical analysis. The results of this study in the first cycle are student learning outcomes showing that ten students who have not reached the Minimum Completion Criteria, while eight students have reached the Minimum Completion Criteria. Result: The results of observations of student learning motivation show that the percentage of science learning motivation is in sufficient category. The results of the study in the second cycle are that only two students are incomplete Minimum Completion Criteria, and sixteen students are declared complete. The results of observations of the learning motivation of fourth grade students at Klumprit State Elementary School shows that the total average percentage of motivation to learn science is being increase. Conclusion: Thus, it can be concluded that the application of the Experimental Method with a pedagogical deep learning approach can improve students’ learning outcomes and motivation in Science in fourth-grade at elementary school.